2023
DOI: 10.3389/fnins.2023.1260675
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural electrocorticography in nonhuman primates by an implantable wireless device for brain-machine interfaces

Tianfang Yan,
Katsuyoshi Suzuki,
Seiji Kameda
et al.

Abstract: BackgroundSubdural electrocorticography (ECoG) signals have been proposed as a stable, good-quality source for brain-machine interfaces (BMIs), with a higher spatial and temporal resolution than electroencephalography (EEG). However, long-term implantation may lead to chronic inflammatory reactions and connective tissue encapsulation, resulting in a decline in signal recording quality. However, no study has reported the effects of the surrounding tissue on signal recording and device functionality thus far.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Taesung Jung 1 † , Nanyu Zeng 1 † , Jason D. Fabbri 1 , Guy Eichler 2 , Zhe Li 3,4.5 , Konstantin Willeke 3,4,5,6 , Katie E. Wingel 7,8 , Agrita Dubey 7,8 , Rizwan Huq 1 , Mohit Sharma 1 , Yaoxing Hu 1 , Girish Ramakrishnan 1 , Kevin Tien 1 , Paolo Mantovani 2 , Abhinav Parihar 1 , Heyu Yin 1 , Denise Oswalt 8,9,10 , Alexander Misdorp 2 , Ilke Uguz 1 , Tori Shinn 11 , Gabrielle J. Rodriguez 3,4,5 , Cate Nealley 3,4,5 , Ian Gonzales 12 , Michael Roukes 13 , Jeffrey Knecht 14 , Daniel Yoshor 8 , Peter Canoll 15 , Eleonora Spinazzi 12 , Luca P. Carloni 2 , Bijan Pesaran 7,8,9,10 , Saumil Patel 3,4,5 , Brett…”
Section: Stable Chronic In-vivo Recordings From a Fully Wireless Subd...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taesung Jung 1 † , Nanyu Zeng 1 † , Jason D. Fabbri 1 , Guy Eichler 2 , Zhe Li 3,4.5 , Konstantin Willeke 3,4,5,6 , Katie E. Wingel 7,8 , Agrita Dubey 7,8 , Rizwan Huq 1 , Mohit Sharma 1 , Yaoxing Hu 1 , Girish Ramakrishnan 1 , Kevin Tien 1 , Paolo Mantovani 2 , Abhinav Parihar 1 , Heyu Yin 1 , Denise Oswalt 8,9,10 , Alexander Misdorp 2 , Ilke Uguz 1 , Tori Shinn 11 , Gabrielle J. Rodriguez 3,4,5 , Cate Nealley 3,4,5 , Ian Gonzales 12 , Michael Roukes 13 , Jeffrey Knecht 14 , Daniel Yoshor 8 , Peter Canoll 15 , Eleonora Spinazzi 12 , Luca P. Carloni 2 , Bijan Pesaran 7,8,9,10 , Saumil Patel 3,4,5 , Brett…”
Section: Stable Chronic In-vivo Recordings From a Fully Wireless Subd...mentioning
confidence: 99%
“…By recording from the brain surface, ECoG minimizes brain tissue damage while being able to acquire higher signal-to-noise ratio (SNR), higher bandwidth, and more spatially localized signals compared to EEG ( 11 ). In vivo studies have shown that ECoG recordings taken from subdural arrays can remain stable for more than a year ( 12, 13 ), demonstrating the technology’s potential usage in chronic applications. Furthermore, advances in microfabrication techniques continue to improve the spatial resolution of the ECoG electrode array.…”
Section: Introductionmentioning
confidence: 99%